Collective Action dalam Jaringan Implementasi Percepatan Penurunan Stunting di Provinsi Sulawesi Barat - Ridha Rimbawan Abidin, Andi; Thahir Haning, Mohammad; Susanti, Gita; Syahribulan, Syahribulan; Fajar Putera, Arifin (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
West Sulawesi province recorded a stunting rate of 0.3% below East Nusa Tenggara, the highest nationally, far exceeding the national average of 21.6%. This study aims to analyze the implementation of collective action in efforts to reduce stunting in West Sulawesi using Carlsson's Collective Action theory (2000) with six dimensions: Contextual Factors, Problem Definition, Growth and Trust, Participation Factors, Actor Mobilization and Coordination and Control. Using a qualitative approach, data were collected through interviews, observations, and document reviews with informants selected by purposive sampling from among government officials, civil servants, and the community. The results showed three main obstacles to collective action: (1) limited socialization of stunting, especially in rural areas, (2) weak synergy between local government, health workers, and the community, and (3) lack of stakeholder support that causes the program to run sporadically. Factors such as early marriage, lack of health education, and low public awareness also exacerbate the situation. This study recommends inclusive communication strategies, strengthening cross-sector coordination, and increasing shared commitment in stunting interventions.